Radiologic Estimation of Hematoma Volume in Intracerebral Hemorrhage Trial by CT Scan - Zimmerman, R.D.; Maldjian, J.A.; Brun, N.C.; Horvath, B.; Skolnick, B.E. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Therapeutic intervention during the early stages of an intracerebral hemorrhage (ICH) might have value in improving clinical outcomes. During the 73-site International Recombinant Activated Factor VII Intracerebral Hemorrhage Trial, CT techniques were used to monitor the change in hematoma volume in response to treatment. The use of CT imaging technology served 3 functions: to provide accurate measurements of the change in hematoma volume, intraventricular volume (IVH), and edema volume; to evaluate the use of CT scans as a predictor of patient outcomes; and to demonstrate that hematoma volume can serve as a surrogate marker for ICH clinical progression.METHODS: The multicenter clinical trial received institutional review board approval and obtained informed consent from the patient or a legally acceptable representative (waived in a few cases of incapacity, according to local and national regulations). CT scans were used to quantify volumes of hemorrhage and to monitor evolution over a 72-hour period in patients with ICH treated with placebo or 40, 80, or 160 μg/kg of recombinant activated factor VII (rFVIIa). CT image data were transmitted digitally to an imaging laboratory and analyzed by 2 readers masked to patient and treatment data, by using Analyze software, a fully integrated toolkit for interactive display, processing, and measurement of biomedical image data. The use of this software enabled the evaluation of intraclass variability of CT scan interpretations.RESULTS: Interpretations of ICH and IVH volumes of CT scans in patients treated in this study showed minimal intraclass variability. Variability was greatest for interpretations of edema volume.CONCLUSION: These CT assessments of lesions could have value in future early hemostatic interventions in ICH patients.